Impact Factors of Days Open Cost on Dairy Profitability - Mohamed, Zainalabidin; Latif , Ismail Abd; Chizari, Ali (Asian Journal of Agriculture and Rural Development, 2014)
Effort to decrease cost of production is a mainly step to improve profitability at the farm. Hidden cost, specifically, days open cost as a huge part of operation cost in dairy herd is one of important task of the managers. The aim of this study investigate of days open cost to identify, assess and control it. Pregnancy rate, culling rate, death rate, mastitis, lameness and also milk price, feed cost, heifer price, cull price, calf price and veterinary cost are included the fundamental costs which has been considered.